Synergistic Role of Extension and Group Programs in Women Farmers’ Behavior: A Case Study in Sragen - Retna Dewi Lestari; Setyo Rahyunanto; Jashila Nair Mogan; Singgih Purnomo; Sugeng Edi Waluyo (Jurnal Pemberdayaan Masyarakat, 2026)
Women farmers play an important role in agricultural sustainability in Indonesia; however, their participation in decision-making and access to extension services remain limited. Previous studies often examine agricultural extension or farmer group programs separately, providing a limited understanding of their combined influence on women farmers’ behavior. Grounded in the Theory of Planned Behavior (TPB), this study analyzes the role of agricultural extension workers and farmer group activity programs in shaping women farmers’ behavior toward sustainable agriculture. A quantitative descriptive approach was employed, using stratified random sampling, with 120 active women farmers in Sragen Regency, Central Java. Data were collected through structured questionnaires and analyzed using multiple linear regression. The results show that extension workers and group programs do not significantly influence behavior when examined individually; however, their combined effect is significant. These findings extend TPB by showing that integrated institutional support and group-based empowerment more effectively influence behavioral change. Practically, the study highlights the importance of integrated, participatory, and gender-responsive extension programs to support sustainable agriculture in rural areas.